Psychological Effect of Distance Learning during the COVID-19 Pandemic on Accounting Practicum Lesson - Imam Hasan (Journal of Vocational Education Studies, 2022)
This study aims to scrutinize the psychological effects of students participating in distance learning during the COVID-19 pandemic in accounting practicum lessons. The research employed a qualitative approach, with a type of single instrumental case study. Data collected were validated using data (sources) triangulation techniques. Data were then analyzed by the qualitative method of Miles and Huberman models (interactive models). The results revealed that distance learning affected students psychology. The psychological effects felt by students, among others, were that distance learning felt less than maximal, less fun, boring, making academic stress, and disappointing. In addition, because distance learning was done at home, students focus and concentration were easily distracted with other things, and student learning motivation fluctuated. Regarding time management, some students could do it, and some others encountered difficulties. A feeling of anxiety and depression was experienced by some students, while others could control them. However, apart from those, distance learning made learning not tense and provided sufficient time for students to relax and refresh.